The new concept of periodontal disease pathogenesis requires new and novel therapeutic strategies - Martin A. Taubman (Blackwell Synergy, 2007)
In this issue Bostanci et al. (2007) demonstrate that receptor activator of NF-kB ligand (RANKL) and osteoprotegerin (OPG) were oppositely regulated in gingival crevice fluid (GCF) from periodontitis patients. RANKL, RANK and OPG are key molecules that regulate osteoclast recruitment, differentiation and activation. New concepts of the pathogenesis of periodontitis have implicated inflammation triggered by host immune response to periodontal biofilm microorganisms(s) in disease. Host response to bacteria involves activation of T and B cells in the inflammatory infiltrate which bear abundant RANKL that promotes osteoclastic bone resorption. Periodontal tissue destruction can be ameliorated by immunobiological interference with immune cell RANKL expression or function. The new disease concepts provide a foundation to build biological approaches to target RANKL production in periodontal lesions.